The Influence of Islamic Marketing Ethics on Customer Interest in Using Mudharabah Savings Products at BMT Ar-Rahmah Arta Syariah Mojokerto - Novarina Amalia Anggraini; Yayuk Sri Rahayu (Universitas Muhammadiyah Sidoarjo, 2022)
It intends to examine the effect of shiddiq, al-adl, al-Amanah, service, and piety on consumer interest in utilizing mudharabah savings products both partially and concurrently in scientific writing. BMT Ar-Rahmah Arta Syariah Mojokerto is the subject of this study, which will take place between 2021 and 2022. The method employed is multiple linear regression analysis, and the type of research used is a quantitative research using more than one variable. Classic assumption tests, multiple linear regression equation tests, and hypothesis testing are examples of multiple linear regression analysis methods. Siddiq (X1), Al-Adl (X2), Al-Amanah (X3), Service (X4), and Takwa (X5) were the five independent variables in this study (X5). The interest of customers in adopting the mudharabah deposit product is the dependent variable (Y). Siddiq, al-adl, al-Amanah, service, and take all had partial and simultaneous effects on customer interest in adopting mudharabah savings products, according to the findings